Rancangan Monitoring Peralatan Transmitter Very High Frequency PAE T6T Berbasis Web Server - Tri Cahyani; Oke Hendra; Rini Sadiatmi; Wildan Nugraha; M Fathar Habillah (Journal of Airport Engineering Technology (JAET), 2021)
The design made has the aim of simplifying the tasks of all technicians and field coordinators in monitoring the operation of VHF Transmitter conditions, so that they canbe controlled anywhere. The background of this research is based on a case that has happened at Perum LPPNPI Kulonprogo Branch, where the VHF Transmitter Building is far from the technician's standby room. When a problem occurs, the technician cannot immediately find out. Therefore, the authors are interested in conducting research with the type of Research and Development (R & D) that uses qualitative research methods. This study resulted in the conclusion that with the main control of the microcontrollerand using a sensor to extract the voltage value from the alarm LED voltage line, so that this design can work and function properly according to the author's expectations.